POLITICAL RHETORIC RELATED TO IMMIGRATION IN THE 2017 FRENCH PRESIDENTIAL CAMPAIGN - Aisyah, Siti; Miranda, Airin (International Review of Humanities Studies, 2021)
This article discusses the political rhetoric regarding immigration and the presence of immigrants declared by the French presidential candidates in the 2017 French presidential election. The issue of immigration is one of the most important aspects of French domestic and foreign policy. The purpose of this study is to determine the perceptions and acceptance of immigrants from the 2017 French presidential candidates, and their impact on the French public. The theory used in this research is Norman Fairclough's three-dimensional models, namely the microstructural, mesostructural, and macrostructural dimensions. The data taken is the first source in the form of newspapers, online media, books, and journal articles. The results of this study indicate that the political rhetoric by presidential candidates in the 2017 French presidential election campaign forms its own identity and acceptance of immigrants in the French public view. Five French presidential candidates presented rhetoric related to immigration and the existence of immigrants with different framing according to the party ideology they adhere to. However, the rhetoric presented by presidential candidate Macron from En Marche! is more acceptable to French society than other presidential candidates.